Pendekatan Participatory Rural Appraisal: Pemetaan Kerentanan Sosial-Ekologi Petani Padi dan Sawit - Aldian Satria Kesuma; Merli .; Putri Nabila; M Gading Laksono; Kevin Dwi Prasetya; Ade Yudistira; Agustina Dwi Putri Situmeang; Afidatu Tsaniyah; Nadilah Dhiya Karimah; Anisah Friti Anjelia; Saprinurdin . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
The complexity of vulnerabilities in agrarian rural areas necessitates an integrative approach to mapping socio-economic and public health issues. This study aims to identify and formulate the root causes of the problems in Padang Peri Village, Seluma Regency. A qualitative action research design based on the Participatory Rural Appraisal (PRA) method was applied. Data collection involved Focus Group Discussions (FGD), participatory mapping, transect walks, and problem tree analysis with local farmers. The results identified three main problem clusters: (1) the failure of pest control prompting excessive chemical spraying; (2) the degradation of soil biophysics due to irrigation deficits accelerating land conversion from rice fields to oil palm plantations; and (3) price fluctuations of palm oil and rice weakening household income. These clusters form an "agricultural-health trap," where economic pressures and ecological damages transmit directly into physical health burdens (chronic pesticide poisoning) and mental health disorders (psychosocial stress). This study recommends strengthening village institutions (BUMDes), accelerating irrigation network development, and transitioning towards ecological agriculture to break the vulnerability chain.